DEVELOPMENT OF LEARNING MEDIA ON THE MATERIAL OF PRACTICING PANCASILA VALUES IN THE FORM OF A SCRAPBOOK FOR FOURTH GRADE STUDENTS AT SD NEGERI 101961 TIMBANG DELI FOR THE 2023/2024 ACADEMIC YEAR - Khairiyah, Salwa; Putri, Nizmi (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2024)
This research aims to: (1) Determine the development of learning media on the material of practicing Pancasila values in the form of a scrapbook for fourth-grade students, and (2) Assess the feasibility of the learning media developed on the same material. This study employs a Research and Development (R&D) methodology. The subjects of the research are 25 fourth-grade students from SD Negeri 101961 Timbang Deli, consisting of 11 boys and 14 girls. According to the material experts' assessment, the feasibility percentage is 94%, categorized as "Highly Feasible." The media experts' assessment shows a feasibility percentage of 96%, also categorized as "Highly Feasible." Student responses from the trials indicate a feasibility percentage of 91.04%, classified as "Highly Feasible." Similarly, based on teacher feedback, the feasibility percentage is 90.7%, with the same classification of "Highly Feasible." The media has been validated by both media and material experts, and it is deemed highly suitable for use as a learning tool for the material on practicing Pancasila values in the form of a scrapbook for fourth-grade students at SD Negeri 101961 Timbang Deli.